Evaluation of polyetheretherketone composites modified by calcium silicate and carbon nanotubes for bone regeneration: mechanical properties, biomineralization and induction of osteoblasts - Cao, Jianfei; Yang, Shuhao; Liao, Yijun; Wang, Yao; He, Jian; Xiong, Chengdong; Shi, Kun; Hu, Xulin (Frontiers in Bioengineering and Biotechnology, 2023)
Desired orthopedic implant materials must have a good biological activity and possess appropriate mechanical property that correspond to those of human bone. Although polyetheretherketone (PEEK) has displayed a promising application prospect in musculoskeletal and dentistry reconstruction thanks to its non-biodegradability and good biocompatibility in the body, the poor osseointegration and insufficient mechanical strength have significantly limited its application in the repair of load-bearing bones and surgical operations. In this study, carbon nanotubes (CNT)/calcium silicate (CS)/polyetheretherketone ternary composites were fabricated for the first time. The addition of CS was mainly aimed at improving biological activities and surface hydrophilicity, but it inevitably compromised the mechanical strength of PEEK. CNT can reinforce the composites even when brittle CS was introduced and further upgraded the biocompatibility of PEEK. The CNT/CS/PEEK composites exhibited higher mechanical strengths in tensile and bending tests, 64% and 90% higher than those of brittle CS/PEEK binary composites. Besides, after incorporation of CNT and CS into PEEK, the hydrophilicity, surface roughness and ability to induce apatite-layer deposition were significantly enhanced. More importantly, the adhesion, proliferation, and osteogenic differentiation of mouse embryo osteoblasts were effectively promoted on CNT/CS/PEEK composites. In contrast to PEEK, these composites exhibited a more satisfactory biocompatibility and osteoinductive activity. Overall, these results demonstrate that ternary CNT/CS/PEEK composites have the potential to serve as a feasible substitute to conventional metal alloys in musculoskeletal regeneration and orthopedic implantation.